Measuring Preschoolers' Executive Function Through Performance-Based Measures and Parent Reports: A Longitudinal Study. - Contreras Solorzano, Alejandra; Kim, Yaewon; Graves, Abigail Reid; Garcia-Barrera, Mauricio A.; Müller, Ulrich (Psychological Assessment, 2026)
Executive function (EF) refers to a set of higher order cognitive skills that undergo significant development during the preschool years and are linked to socioemotional and behavioral outcomes. EF is typically assessed through performance-based tasks (PBT) and informant ratings, such as the Behavior Rating Inventory of Executive Function–Preschool (BRIEF-P) Version. However, cross-sectional studies often find low or nonsignificant associations between these two methods. This longitudinal study examined the concurrent and longitudinal associations between PBT and BRIEF-P across three time points, each 6 months apart. Participants were 110 preschool-aged children (36–47 months; M = 40.54, SD = 3.27; 48% female; 85% White) who completed five PBT at each time point. Parents also completed the BRIEF-P and provided socioemotional and behavioral ratings at Time 3. Growth models assessed associations between measurement methods, EF changes over time, and the prediction of outcomes. Consistent with prior findings, PBT composites and BRIEF-P parent rating correlations were low (−.30 to.03 with a median r =.07). Only PBT scores improved over time (β =.075, SE =.008, p <.001), while only BRIEF-P scores predicted behavioral difficulties, lower prosocial behavior, and other executive-related outcomes. Since outcomes were also parent-reported, the link between parent-rated EF and these outcomes may reflect shared method variance. Findings underscore the importance of using multiple methods to assess EF. Public Significance Statement: Our findings suggest that children's performance-based and parent-rated measures of executive function (EF) capture different aspects of development. Across 1 year, children's EF performance improved, whereas parent ratings remained stable. Only parent-rated EF was associated with parent-rated outcomes, underscoring the importance of selecting EF measures that align with the study's intended focus and outcomes.